Personalizing prenatal care using family health history: identifying a panel of conditions for a novel electronic genetic screening tool. (May 2013) - Lin, Bruce K; Edelman, Emily; McInerney, Joseph D; O'Leary, James; Edelson, Vaughn; Hughes, Kevin S; Drohan, Brian; Kyler, Penny; Lloyd-Puryear, Michele; Scott, Joan; Dolan, Siobhan M
In the age of genomic medicine, family health history (FHH) remains an important tool for personalized risk assessment as it can inform approaches to disease prevention and management. In primary care, including in prenatal settings, providers recognize that FHH enables them to assess the risk for birth defects and complex conditions that not only affect the fetus health, but also the mother's. However, many providers lack the time to gather FHH or the knowledge to confidently interpret the data. Electronic tools providing clinical decision support using FHH data can aid the busy provider with data collection and interpretation. We describe the scope of conditions included in a patient-entered FHH tool that provides clinical decision support and point-of-care education to assist with patient management. This report details how we selected the conditions for which it is appropriate to use FHH as a means to promote personalized medicine in primary prenatal care.